STUDY OF METAVERSE: INFLUENCE OF DISCORD VIRTUAL COMMUNITY TO PURCHASE INTENTION OF NON-FUNGIBLE TOKEN (NFT) - Maria Dini Gilang Prathivi; Adrie Oktavio (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. A wide range of NFTs as non-interchangeable token of data saved on a blockchain which are being sold and being widely shared on digital platforms. Having a unique characteristic, NFT branding and its promotional activity to let them know by the public has been done in social media, particularly Twitter as a meaning of public perception building and potential buyers collecting effort. But the author found that the role of company initiated virtual community in Discord has a big impact as it gathers targeted group and building connection between the company and the people who has probability to purchase in the future - that is going to be examined in this research using E-WOM as the mediation. By finishing this study, the author digs into the study of metaverse as the metaverse could be the future development of the Internet based on its tenacious, shared virtual worlds in which people interact as 3D avatars. Blockchain technology may represents the very essence of the metaverse to the fact that linked NFT assets that can be used thorough different metaverse platforms.Abstrak. Berbagai macam NFT sebagai token data yang tidak dapat dipertukarkan yang disimpan di blockchain yang dijual dan dibagikan secara luas di platform digital. Memiliki karakteristik yang unik, NFT branding dan aktivitas promosinya untuk diketahui oleh publik telah dilakukan di media sosial, khususnya Twitter sebagai sarana untuk membangun persepsi publik dan upaya pengumpulan pembeli potensial. Tetapi penulis menemukan bahwa peran komunitas virtual yang diprakarsai perusahaan dalam Discord memiliki dampak besar karena mengumpulkan kelompok sasaran dan membangun hubungan antara perusahaan dan orang-orang yang memiliki kemungkinan untuk membeli di masa depan - yang akan diteliti dalam penelitian ini. menggunakan E-WOM sebagai mediasi. Dengan menyelesaikan studi ini, penulis menggali studi tentang metaverse karena metaverse bisa menjadi pengembangan masa depan Internet berdasarkan dunia maya yang ulet dan berbagi di mana orang-orang berinteraksi sebagai avatar 3D. Teknologi Blockchain dapat mewakili inti dari metaverse dengan fakta bahwa aset NFT terkait yang dapat digunakan melalui platform metaverse yang berbeda.